Chemical composition of wet deposition in a Mediterranean site Athens, Greece related to the origin of air masses - Nastos, P. T.; Alexakis, D.; Kanellopoulou, H. A.; Kelepertsis, A. E. (Journal of Atmospheric Chemistry, 2007)
The goal of this study is to determine the chemical composition of rain, in the wider region of Athens, Greece for the time period 1st September 2001 to 31st August 2002. Two model automatic rain samplers were installed in the Meteorological Station of Laboratory of Climatology (latitude: 37Β° 58β€² N, longitude: 23Β° 47β€² E) inside the Athens University Campus and in a site at Heraklio Attica, a northern suburb of Athens (latitude: 38Β° 03β€² N, longitude: 23Β° 45β€² E). The concentrations (ΞΌeq l -1) of the major cations (H +, Na +, K +, Ca 2+ and Mg 2+) and anions (Cl -, NO 3 -, HCO 3 - ΞΊΞ±ΞΉ SO 4 2-, as well as pH and conductivity of rain in 39 total samples were determined. The figures of pH range from 6.4 to 8.4 and conductivity from 8 to 207 ΞΌS cm -1. The analysis showed that Ca 2+ ions are abundant within all examined samples, while HCO 3 - and SO 4 2- present the highest concentrations from the anions. In order to find out the origin of the air masses, the air mass back trajectories were calculated. Five sectors of the origin of air masses were revealed: the North, the South, the Local, the West and the East sector. Multivariate methods included Factor Analysis and Discriminant Analysis were applied to the examined ion concentrations and three main factors were extracted, which discriminated the ions according to their origin. The first group of ions is interpreted as the result of the anthropogenic activity, the second group represents the acidity-alkalinity independently of their source and the third one the marine influence. Β© 2007 Springer Science+Business Media B.V.
Keywords: air; air mass; Air mass back trajectories; anion; article; Athens [Attica]; Attica; calcium; calcium ion; carbonic acid; cation; chemical composition; chemical model; chloride; concentration (parameters); conductance; conductivity; Discriminant analysis; Eurasia; Europe; Factor analysis; factorial analysis; Greece; human activity; hydrogen; laboratory method; magnesium; Major anions; Major cations; Mediterranean environment; Multivariate Analysis; nitrate; pH; potassium; rainwater; sodium; Southern Europe; sulfuric acid; trajectory; water sampling; Wet deposition